Development of mechanical, electrical and electromechanical properties of copolymer styrene-butadiene-styrene with carbon nanotubes composites - Costa, Pedro Filipe Ribeiro (2013)
Tese de doutoramento (Programa Doutoral em Engenharia de Materiais)